Effect of Power and Type of Substrate on Calcium-Phosphate Coating Morphology and Microhardness; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Kulyashova K. Ksenia; Sharkeev Yu. P. Yury Petrovich; Glushko Yu. Yurii; Sainova A. Aizhan (2015, 2015)
Title screen